9 - Reflection on student drop-out against the backdrop of COVID-19 in the South African Educational context amongst marginalised groups of students: Peggy Pinky Mthalane, Albert Tchey Agbenyegah & Bongani Innocent Dlamini - Peggy Pinky Mthalane; Albert Tchey Agbenyegah; Bongani Innocent Dlamini (African Sociological Review, 2021)
This paper aims to engage the issue of student drop-out in light of COVID-19 which has disrupted schooling at all levels and impacts heavily on students from deprived background who do not have access to technology that have become the dominant means of teaching. In engaging the issue, the paper reviews the literature on student drop-out generally to highlight the factors that have been shown to be significant in student dropping out of school at primary, secondary and university levels.